Immunologic Adverse Reaction Associated with Low-carbide Metal-on-metal Bearings in Total Hip Arthroplasty - Aroukatos, Panagiotis; Repanti, Maria; Repantis, Thomas; Bravou, Vassiliki; Korovessis, Panagiotis (Clinical orthopaedics and related research, 2010)
Background An increased incidence of periprosthetic osteolysis, resulting in loss of biologic fixation, has been reported in contemporary THAs with low-carbide metal-on-metal compared with metal-on-polyethylene couple bearings. Although a hypersensitivity reaction attributable to Co and Cr debris is reportedly a potential cause for failure of THAs with high-carbide bearings, there are no evidence-based data for this reaction in low-carbide metal-on-metal bearings, although such hypersensitivity might be related to osteolysis. Questions/purposes We investigated whether there were differences in immunologic hypersensitivity reactions in retrievals from revised THAs with ceramic-on-polyethylene versus metal-on-metal bearing couples. Patients and Methods We compared newly formed capsule and periprosthetic interface membranes from revision surgery for aseptic failure from 20 patients with low-carbide bearings and 13 patients with ceramic-on-polyethylene bearings. For control tissue, we obtained samples from the hip capsule during the primary THA implantation in 13 patients with low-carbide bearings and seven with ceramic-on-polyethylene bearings. We examined the tissues with conventional histologic and immunohistochemical methods. Results Compared with tissue from the control subjects and patients with ceramic-on-polyethylene bearings, the tissues from patients with low-carbide metal-on-metal bearings were associated with (1) extensive necrosis and fibrin exudation in the newly formed hip capsule and (2) diffuse and perivascular lymphocytic infiltration of a higher degree than in the hips with ceramic-on-polyethylene bearings in conventional histologic examination, and (3) more T than B cells. Conclusions The conventional histologic and immunohistochemical findings in tissues retrieved from failed THAs with low-carbide metal-on-metal bearings are consistent with a link between hypersensitivity and osteolysis with low-carbide bearing couples.